Segmentation of Salient Flying Objects in Complex Sky Scene using Reconstruction Morphological Operations - Sandeep, Sandeep; Suresha, M (International Journal of Computer Sciences and Engineering, 2025)
Salient object segmentation is useful for supervised learning process. The challenging issues of this work is small flying object Segmentation in different lighting condition in the sky images using Morphological Closing and reconstruction techniques. In the proposed method, detection of regional maximal in grey level image with specified connectivity and removing of borders, filled holes. Finally, identifies flying object and gives fast processing and effective results. Experimental results on dataset demonstrates the proposed techniques performs well against existing methods